Redução de danos, política do comum e invenções de um cuidado de si: uma cartografia do Centro de Convivência É De Lei - Vaz, Rodrigo de Oliveira Feitosa (2015)
This thesis deals with the practices of care on harm reduction (forged in a context/field of fights) that challenges its constitution as an effective common policy for alcohol and other drugs. The Cartographic attention used as a methodology in this study, sets out to follow the daily life of care practices in harm reduction undertaken by a living center for drug users in social vulnerability in the city of São Paulo - Centro de Convivência É de Lei. The following activities were accompanied and observed in the Center: team meeting; assembly; Chá de Lírio; and video and hip hop workshops. During the activities, a team that produced ways of care was formed through participant observation and daily life conversations (in a way that all participants had a good neighborly relation). From these actions, it was possible to extract some clues for the analysis. It was also used as field analysis the notion of self care in Foucault, and we situated the emergency and the paths of health policies in regard to the use of psychoactive substances and the ways that harm reduction appears in it. Such practices, that we named as cuidar con-vivendo/con-viver cuidando (Care living together / live together care), constitute a certain precarious dimension and challenge, when harm reduction becomes a war machine, a narrow defile. We consider that such proposals of the care center are also affirmed when passing borderlines and crossroads